2022
DOI: 10.3390/en15010284
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Torque Performance and Flux Reversal Reduction of a Three-Phase 12/8 Switched Reluctance Motor Based on Winding Arrangement

Abstract: The goal of this paper is to present a comparative analysis of two types of winding arrangements for a three-phase 12/8 switched reluctance motor (SRM), where short- and fully-pitched winding arrangements under unipolar operation are considered. From the analytical results, the short-pitched winding has the best torque per copper weight ratio. The core loss based on counting the number of flux reversals in the stator yoke for each winding arrangement is also proposed and mentioned. To reduce the magnetic flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…At the same time, the cost of rare earth magnets is high, they are supplied by only a few suppliers, the raw material extraction process for their manufacture is harmful to the environment and there are problems with disposal. This gives good motivation for developing electric machines without rare earth magnets [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the cost of rare earth magnets is high, they are supplied by only a few suppliers, the raw material extraction process for their manufacture is harmful to the environment and there are problems with disposal. This gives good motivation for developing electric machines without rare earth magnets [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…The results of testing the motor at the rated load are provided, verifying the theoretical results obtained. In [6], two winding layouts of a three-phase switched reluctance motor (SRM) with twelve stator teeth and eight rotor teeth are compared in terms of power loss and efficiency. It is shown that the winding with a short pitch provides a lower copper of loss than the winding with a full pitch.…”
mentioning
confidence: 99%